Cho $\Large \int{2x{{(3x-2)}^{6}}dx=A{{(3x-2)}^{8}}+B{{(3x-2)}^{7}}+C}

Cho $\Large \int{2x{{(3x-2)}^{6}}dx=A{{(3x-2)}^{8}}+B{{(3x-2)}^{7}}+C}

4.3/5

Tác giả: Thầy Tùng

Đăng ngày: 18 Aug 2022

Lưu về Facebook:

Câu hỏi:

Cho $\Large \int{2x{{(3x-2)}^{6}}dx=A{{(3x-2)}^{8}}+B{{(3x-2)}^{7}}+C}$ với $\Large A,B\in Q$ và $\Large C\in R$. Giá trị của biểu thức $\Large 12A+7B$ bằng

Đáp án án đúng là: D

Lời giải chi tiết:

Đặt $\Large t=3x-2\Rightarrow x=\dfrac{t+2}{3}\Rightarrow \dfrac{1}{3}dt=dx$

Ta có $\Large \int{2x{{(3x-2)}^{6}}dx=\dfrac{2}{3}}\int{\dfrac{t+2}{3}}.{{t}^{6}}dt=\dfrac{2}{9}\int{\left( {{t}^{7}}+2{{t}^{6}} \right)dt=\dfrac{2}{9}.\dfrac{{{t}^{8}}}{8}+\dfrac{4}{9}.\dfrac{{{t}^{7}}}{7}+C}$ 

$\Large =\dfrac{1}{36}.{{(3x-2)}^{8}}+\dfrac{4}{63}.{{(3x-2)}^{7}}+C$

Suy ra $\Large A=\dfrac{1}{36},B=\dfrac{4}{63}$

Giá trị của biểu thức $\Large 12A+7B=12.\dfrac{1}{36}+7.\dfrac{4}{63}=\dfrac{7}{9}$

Chọn đáp án D